1998
DOI: 10.1038/35385
|View full text |Cite
|
Sign up to set email alerts
|

Blocking apoptosis prevents blindness in Drosophila retinal degeneration mutants

Abstract: Apoptosis is a gene-directed form of cell death that is essential for normal development and health. Yet abnormally high levels of apoptosis are linked to many degenerative diseases. Some important biochemical events in apoptosis have been identified, but the therapeutic utility of blocking cell death remains unclear. An important question in this regard is whether cells rescued from apoptosis can function. We have investigated the mechanism of cell death in two Drosophila mutant strains that exhibit age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 28 publications
3
94
0
Order By: Relevance
“…Despite the diversity in mechanisms underlying photoreceptor cell death in Drosophila, many of the retinal degenerations show features of apoptosis, which is reminiscent of human retinal dystrophies [31,98,234,235]. Although a lot of progress has been made over the past few years, there remain many unanswered questions regarding the mechanisms of retinal degeneration in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the diversity in mechanisms underlying photoreceptor cell death in Drosophila, many of the retinal degenerations show features of apoptosis, which is reminiscent of human retinal dystrophies [31,98,234,235]. Although a lot of progress has been made over the past few years, there remain many unanswered questions regarding the mechanisms of retinal degeneration in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that the baculoviral caspase inhibitor, p35, was not only capable of preventing apoptosis in retinal degenerative Drosophila mutants, but also of maintaining visual functionality. 61 Interestingly, a recent report has attributed an anti-oxidant property to p35 62 suggesting that cell survival in these retinal degenerative mutants may not only require inhibition of the effectors of the cell death machinery, but also of the initiating signals. In light of this view, and as our findings demonstrate, the use of antioxidants may be of more therapeutic benefit in the prevention of retinal degeneration in RP than inhibitors of the caspases.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, p35 effectively inhibits a broad range of active caspases and can block cell death not only in insects, but also in C. elegans, vertebrates, and plants (Danon et al 2004;Izquierdo et al 1999;Xue and Horvitz 1995;Sugimoto et al 1994). In Drosophila, targeted expression of p35 blocks both naturally occurring developmental cell death as well as ectopic cell death induced by genetic or environmental means (Davidson and Steller 1998;Hay et al 1994).…”
mentioning
confidence: 99%